ANALISIS PERAN LITERASI DIGITAL SEBAGAI WADAH PENDIDIKAN POLITIK DALAM MENGURANGI SIFAT APOLITIS (STUDI KASUS: SMKN 39 JAKARTA PUSAT PADA PEMILU TAHUN 2019) - Agrenisa Pratiwi (2023)
This study aims to describe the implementation of political education which is rarely encountered by the younger generation, especially in technical vocational schools at SMKN 39 Central Jakarta. The lack of political education by the younger generation who are still in vocational schools has led to an apolitical attitude towards politics, especially on issues leading up to the 2019 simultaneous elections. Given these problems, this research will discuss the role of digital media as an increase in political literacy through political education based on digital by using the theory of political communication and political education, as well as the concept of digital literacy, the role of digital media and apathy. This study uses a combination approach (mix method) with sequential explanatory types and uses primary and secondary data sources. There are two ways to collect data, namely the quantitative method through questionnaires and qualitative methods through interviews and documentation with data processing techniques, namely through the help of SPSS type 23.0 for windows as well as data reduction, data presentation, and drawing conclusions. The research results found from this study are that quantitatively there is a relationship between political education and digital literacy in reducing apolitical traits, while qualitative results were obtained through interviews with key informants namely DKI JAKARTA Province Bawaslu Members, DKI JAKARTA Provincial DPRD Members, DKI Provincial Education Office JAKARTA and representatives of PKN Teachers at SMKN 39 JAKARTA PUSAT regarding the role of digital literacy as an educational forum in reducing the apolitical nature of the younger generation, there is a discussion related to political education needed by the younger generation, appropriate political communication strategies to make it easier for the younger generation to understand political education information through digital , being active in collaboration with government agencies and the impact of the presence of digital political literacy in assisting the role of the KPU and Bawaslu in reducing the apolitical nature of the younger generation towards political and electoral issues. Keywords: Political Communication, Political Education, Digital Literacy